Síntese de N-Alquilsulfonamidas análogas do PABA com potencial atividade antagonista de canais iônicos - Martins, Carina Couto [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The development of new drugs more efficient, less toxic and with fewer side effects has been a subject of great importance and scientific interest. Un this context the present work shows the sythesis of new sulfonated compounds analogues of PABA, with potential interesting pharmacological properties, as the effect or blocking activity on ion channels of voltage gated potassium. In addition, some of these sufonamides, have N-(aminoalkyl) lactams as side chain. These lactamic groups have been described as inhibitors of human tryptase, an important mediator in asthma, and activity as HIV-1 protease inhibitors. The physical-chemical analyses have been carried out by different spectrocopic (1H and 13C NMR, FT-IR) and spectrometric techniques (EI-MS and ESI-MS). The structures of all compounds were unambiguously confirmed. A study for High Resolution Mass Spectrometry was peformed for all products. This study allowed to observe the formation of sulfoxylates ions and to propouse mechanisms to explain this and other experimental fragments. The synthesized molecules are under current investigation of its inhibiting channels and some molecules showed good results

O desenvolvimento de novos fármacos mais eficientes, menos tóxicos e com menores efeitos colaterais, tem se mostrado um tema de grande importância e interesse científico. Neste contexto o presente trabalho apresenta a síntese de N-alquilsulfonamidas análogos do PABA, com potencial propriedades farmacológicas interessantes como efeito ou atividade bloqueadora sobre canais iônicos de potássio dependentes de voltagem. Além disso, algumas dessas sulfonamidas sintetizadas apresentam N-(aminoalquil)-lactamas como cadeia lateral. Estes grupos lactânicos que têm sido descritos como inibidores de tryptase humana, um mediador importante na asma, e atividade como inibidores de protease do HIV-1. As análises físico-químicas foram realizadas por diferentes técnicas espectroscópicas (RMN de 1H e 13C, FT-IR) e espectrométricas (EI-MS e ESI-MS). As estruturasde todos os compostos foram confirmadas sem ambiguidade. Foi realizado um estudo por espectrometria de massas de alta resolução para todos os produtos. Esse estudo permitiu observar a formação do íon sulfoxilato e propor mecanismos para explicar este e outros fragmentos experimentais. As moléculas sintetizadas estão sob investigação para determinar sua atividade inibitória de canais de potássio. Algumas moléculas mostraram bons resultados
Keywords: Ciência dos materiais; Sulfonamidas; Espectrometria de massa; Canais ionicos; Materials science